(untitled) (Academicia Globe: Inderscience Research, 2023)
The theoretical foundations of empirical model construction and forecasting mechanisms using systematic analysis and digital technologies to ensure macroeconomic stability of agricultural production development have been improved. The level of effective use of the main production resources, or more generally, the level of use of the existing potential, in ensuring the macroeconomic stability of the development of agricultural production.